2014
DOI: 10.2196/medinform.3555
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Personal Single Nucleotide Polymorphism (SNP) Data into a National Level Electronic Health Record for Disease Risk Assessment, Part 2: The Incorporation of SNP into the National Health Information System of Turkey

Abstract: BackgroundA personalized medicine approach provides opportunities for predictive and preventive medicine. Using genomic, clinical, environmental, and behavioral data, the tracking and management of individual wellness is possible. A prolific way to carry this personalized approach into routine practices can be accomplished by integrating clinical interpretations of genomic variations into electronic medical record (EMR)s/electronic health record (EHR)s systems. Today, various central EHR infrastructures have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In envirobehavioral and clinical evaluation, it was found that patient “03-huD889CC” had previously been diagnosed with syphilis. In prior publications, syphilis has been reported as a risk factor for prostate cancer [ 2 ]. The healthy individuals, who had a higher risk than controls, namely “06-hu56B3B6”, had basal cell carcinoma, and “21-huAC827A” had hypogonadism, that is a low level of testosterone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In envirobehavioral and clinical evaluation, it was found that patient “03-huD889CC” had previously been diagnosed with syphilis. In prior publications, syphilis has been reported as a risk factor for prostate cancer [ 2 ]. The healthy individuals, who had a higher risk than controls, namely “06-hu56B3B6”, had basal cell carcinoma, and “21-huAC827A” had hypogonadism, that is a low level of testosterone.…”
Section: Resultsmentioning
confidence: 99%
“…The healthy individuals, who had a higher risk than controls, namely “06-hu56B3B6”, had basal cell carcinoma, and “21-huAC827A” had hypogonadism, that is a low level of testosterone. And both of these clinical conditions are known to decrease the prostate cancer risk [ 1 , 2 ]. Also, “06-hu56B3B6” and “17-huA720D3” used several risky, protective drugs and supplements regarding prostate cancer risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, as an initial attempt to develop a sophisticated infrastructure, we focused to incorporate the personal SNP data into NHIS-T for disease risk assessment, and evaluated the performance of various predictive models for prostate cancer cases. We presented our work as three parts: (1) a literature review for requirements, (2) the incorporation of SNP into the NHIS-T [ 18 ], and (3) an evaluation of SNP incorporated into NHIS-T for prostate cancer [ 19 ]. In this part, the scientific literature was reviewed, and the requirements were extracted regarding SNP data integrated EMRs/EHRs.…”
Section: Introductionmentioning
confidence: 99%
“…Many institutions have adopted genetic testing as part of clinical care, with some exploring how computable representations of genetic and genomic results in the electronic health record (EHR) can facilitate clinical decision support (CDS). [1][2][3][4][5][6][7][8] However, despite established standards for the computable representation of these results, 9 this level of integration has not seen wide adoption outside of the research setting. 10,11 Genetic test results are generally returned as a plain-text representation of the interpretation report and transmitted using the Health Level 7 (HL7) v2 standard, or more commonly as PDFs that must be scanned from a fax or downloaded from an external laboratory portal.…”
mentioning
confidence: 99%